Analisis Prosedur Pemberhentian Perangkat Desa di Desa Transpatoa Kecamatan Helumo Kabupaten Bolaang Mongondow Selatan - Rizal La-nggolu (CV Rewang Rencang, 2025)
Currently, the phenomenon of dismissal of Village Officials is rampant. Transpatoa Village, Helumo District, South Bolaang Mongondow Regency is no exception. The Transpatoa Village Head dismissed the Village Official, who was the hamlet head in the village, without following the procedures stipulated in the Village Law and the Minister of Home Affairs Regulation concerning the Appointment and Dismissal of Village Officials. Therefore, a systematic and structured study is needed to determine the actual mechanism for dismissing Village Officials based on the review of Minister of Home Affairs Regulation Number 67 of 2017. This study, using empirical legal research, found that the dismissal of Village Officials in Tranpatoa Village did not comply with the procedures stipulated in the law.